The effect of fertilising pinus radiata stands at mid rotation age in the Western Cape Province on leaf area, growth efficiency and stand productivity - Badenhorst, Johannes Jurie (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2010.